Bioinformatics: An Indroduction - Jeremy J. Ramsden; Jeremy J. Ramsden (New Delhi Springer, 2006)
The tittle book attempts to give a self- contained account of bioinformatics, so that the newcomer to the field may , whatever his point of depture, gain rather complete overview.
Information Biology Application
Keywords: Information ,Biology ,Application